Spectral lines evolution in the media illuminated by non-stationary energy sources - Nikoghossian, A.
A brief review of the author’s recent work on the development and application of the theory of time-dependent transfer of radiation in the spectral line is given. Various factors that influence the temporal characteristics of changes in line spectra are studied. This creates a fundamental opportunity to use them to gain insight into both external energy sources, the physical and geometrical properties of the medium itself as well as the various optical parameters of the observed spectral lines.
Keywords: Astronomy